2022
DOI: 10.15252/emmm.202115377
|View full text |Cite
|
Sign up to set email alerts
|

TPC2 rescues lysosomal storage in mucolipidosis type IV , Niemann–Pick type C1, and Batten disease

Abstract: Lysosomes are cell organelles that degrade macromolecules to recycle their components. If lysosomal degradative function is impaired, e.g., due to mutations in lysosomal enzymes or membrane proteins, lysosomal storage diseases (LSDs) can develop. LSDs manifest often with neurodegenerative symptoms, typically starting in early childhood, and going along with a strongly reduced life expectancy and quality of life. We show here that small molecule activation of the Ca2+‐permeable endolysosomal two‐pore channel 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…A recent report failed to show a lysosomal cholesterol accumulation in human JNCL fibroblasts using filipin staining. 40 Lipofuscin deposition may interfere with filipin signal in this model. It is also possible that cholesterol may accumulate more readily in brain cell types than in fibroblasts.…”
Section: Discussionmentioning
confidence: 83%
“…A recent report failed to show a lysosomal cholesterol accumulation in human JNCL fibroblasts using filipin staining. 40 Lipofuscin deposition may interfere with filipin signal in this model. It is also possible that cholesterol may accumulate more readily in brain cell types than in fibroblasts.…”
Section: Discussionmentioning
confidence: 83%
“…TPC2-A1-N may also be useful in contexts in which more distal defects may impair NAADP-evoked Ca 2+ release, for example, deficiencies in enzymes, such as CD38, SARM1, and/or DUOX, that promote NAADP synthesis and play roles in immune dysfunction and neurodegeneration ( 40 ). The ability of TPC2-A1-P to promote autophagy and lysosomal exocytosis has been leveraged to revert lysosomal storage phenotypes in vitro and in vivo ( 41 ). Because TPC2 is activated by both NAADP and PI(3,5)P 2 and coupled to distinct functionally relevant ionic profiles, it is difficult to unequivocally ascribe phenotypic change upon TPC2 blockade to a specific activation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that activating TPC2 with TPC2‐A1‐P can revert lysosomal defects in MLIV and other lysosomal storage disorders (Prat Castro et al., 2022; Scotto Rosato et al., 2022). This was ascribed to enhanced lysosomal exocytosis because TPC2‐A1‐P but not TPC2‐A1‐N had previously been shown to boost lysosomal exocytosis (Gerndt et al., 2020).…”
Section: Introductionmentioning
confidence: 99%